Extended follow‐up of the AdVance XP male sling in the treatment of male urinary stress incontinence after 48 months: Results of a prospective and multicenter study. Issue 7 (11th July 2019) - Grabbert, Markus; Mumm, Jan‐Niclas; Klehr, Benedikt; Kretschmer, Alexander; Gebhartl, Peter; Gozzi, Christian; Homberg, Roland; May, Florian; Rehder, Peter; Stief, Christian G.; Bauer, Ricarda M.
Abstract : Objective: To evaluate the efficacy and safety of the AdVance XP male sling in a midterm follow‐up for the treatment of male urinary incontinence in a selected patient cohort. Materials and Methods: In all, 115 patients with postprostatectomy incontinence were prospectively enrolled. A previous endoscopic evaluation of a sufficient coaptive zone in the repositioning test was mandatory. Patients with urine leakage in supine position or previous incontinence surgery were excluded. Postoperatively a standardized 24‐hour pad test and pad usage were evaluated. To compare pre‐ and postoperative continence status nonparametric t test was used. A P ‐value of <.05 was seen as statistically significant. Results: Median preoperative urine loss in the 24‐hour pad test was 272 g (min. 42‐max. 1600) and was significantly improved at any point in follow‐up. Success was defined as 0 pads per day and a maximum of 5 g in the 24‐hour pad test. After a follow‐up of 48 months, 71.7% of the patients were cured, whereas 15.0% of patients had an improved continence situation and 13.3% were classified as failed. Mean urine loss decreased significantly to 24.4 g ( P  ≤ .001). No severe intra‐ or postoperative complications are to be reported. Median follow‐up was 4.2 years. Conclusions: A stable effectiveness in a selected patient cohort can also be demonstrated in an extended follow‐up. The complication rates are low and no late postoperative complications occurred, indicating the safety of the procedure.